Identity and Temporal Fragmentation in Borderline Personality Disorder: A Systematic Review - Ilaria Faggioli; Cecilia Maria Esposito; Giovanni Stanghellini (Brain Sciences)
Background: Borderline Personality Disorder (BPD) is a prevalent psychopathological condition, affecting 0.7–2.7% of the general population. Given the known link between identity formation and the temporal, metacognitive, and narrative processes that contribute to its coherence, the aim of the present systematic review is to synthesize the current literature about the relationship between identity diffusion and lived time in adult patients with BPD. This would enhance knowledge and treatments, leading to a better understanding of the implications of time processes on identity diffusion in BPD. Methods: According to PRISMA guidelines, the main databases were consulted, and specific eligibility criteria were applied. The selection leads to the inclusion of 15 articles, investigating through integrated techniques the lived time, memory, self-reported narratives, and metacognition in BPD subjects. Results: A general agreement among researchers was found, confirming greater difficulty for BPD subjects in producing autobiographical stories, logically and temporally integrated, characterized by positive content. Functional and structural alterations were detected to explain narrative incoherence, as well as symptoms such as emotional dysregulation and cognitive biases. Conclusions: The difficulty for BPD subjects in producing a coherent personal narrative has been interpreted as a correlation of anomalies in autobiographical memories and consequently identities, which were equally compromised by the experience of discontinuity in the temporal structure. This would confirm the hypothesis of the temporal fragmentation of the self in BPD. Although some limitations have been encountered, we suggest that the understanding of identity diffusion and lived time in BPD subjects could represent a useful guide for further research.